Ideal distribution route: An optimization approximation by using random search method - Arsy, Abdu Afin; Shalih, Faris Alaudin; Al Husein, Fulkan Kafilah; Abdurrazzaq, Achmad (Desimal: Jurnal Matematika, 2024)
Distribution is the process of transferring goods from producers to consumers. In this process, both producers and consumers always expect a more efficient distribution system. One way to create an efficient distribution channel is by determining the ideal point for vital objects. By determining the ideal point, an optimal solution can be obtained in minimizing costs and improving the efficiency of the distribution system. This research discusses the determination of the ideal point using numerical optimization methods. Analytical and numerical approaches are used through the Modified Random Search method to formulate and analyze a mathematical model that can provide an optimal solution to the distribution problem. The proposed algorithm will be implemented to solve the energy distribution problem in the real environment. The aim is to test the effectiveness and accuracy of the proposed algorithm based on the solutions obtained. Based on the experimental results, distribution problems in general and energy distribution in particular are addressed better, and the distribution process is more efficient.